Cardiac troponin elevation and mortality in takotsubo syndrome: New insights from the international takotsubo registry - Stähli, Barbara E; Schindler, Matthias; Schweiger, Victor; Cammann, Victoria L; Szawan, Konrad A; Niederseer, David; Würdinger, Michael; Schönberger, Alexander; Schönberger, Maximilian; Koleva, Iva; Mercier, Julien C; Petkova, Vanya; et al. (European journal of clinical investigation, 2024)
BACKGROUND: The clinical relevance of cardiac troponin (cTn) elevation in takotsubo syndrome (TTS) remains uncertain. The present study sought to investigate the role of cardiac troponin (cTn) elevations in mortality prediction of patients with Takotsubo syndrome (TTS). METHODS: Patients enrolled in the International Takotsubo (InterTAK) Registry from January 2011 to February 2020 with available data on peak cTn levels were included in the analysis. Peak cTn levels during the index hospitalization were used to define clinically relevant myocardial injury. The threshold at which clinically relevant myocardial injury drives mortality at 1 year was identified using restricted cubic spline analysis. RESULTS: Out of 2'938 patients, 222 (7.6%) patients died during 1-year follow-up. A more than 28.8-fold increase of cTn above the upper reference limit was identified as threshold for clinically relevant myocardial injury. The presence of clinically relevant myocardial injury was significantly associated with an increased risk of mortality at 5 years (adjusted HR 1.58, 95% CI 1.18-2.12, p =.002). Clinically relevant myocardial injury was related to an increased 5-year mortality risk in patients with apical TTS (adjusted HR 1.57, 95% CI 1.21-2.03, p =.001), in presence of physical stressors (adjusted HR 1.60, 95% CI 1.22-2.11, p =.001), and in absence of emotional stressors (adjusted HR 1.49, 95% CI, 1.17-1.89, p =.001). CONCLUSION: This study for the first time determined a troponin threshold for the identification of TTS patients at excess risk of mortality. These findings advance risk stratification in TTS and assist in identifying patients in need for close monitoring and follow-up.
Keywords: troponin; Male; Troponin; Troponin T; Aged; mužské pohlaví; senioři; registrace; troponin T; senioři nad 80 let; troponin I; lidé; ženské pohlaví; Humans; Troponin I; Aged, 80 and over; takotsubo kardiomyopatie; Registries; Female; Takotsubo Cardiomyopathy; lidé středního věku; Middle Aged